Sosialisasi terhadap Orang Tua tentang Penggunaan Internet yang Sehat dan Aman bagi Anak-anak - Dewi, Sofia (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2022)
The existence of the internet has separated itself from human life, young and old. Like most internet users, especially social networks that allow them to freely access information and interact with others through cyberspace, can have both positive and negative impacts on children. The negative impact of free and uncontrolled internet use can damage moral and social life. Children are particularly at risk of these negative impacts. It can affect their outlook on life so it becomes a bad trait. This condition requires efforts to avoid and anticipate the bad effects of the internet on children. The main effort should be made by parents as their closest environment. Parents must set limits, monitor, and provide direction to children. Through community service activities that aim to provide education on the importance of the role of parents in supervising the importance of safe and healthy internet. The method of implementing the activities used is the method of counseling or socialization. The implementation of this socialization can maximize the positive impact of internet use and minimize the negative impact.